Pediatric Trauma Care A Practical Guide - Kennedy Jr, Alfred P.; Ignacio, Romeo C.; Ricca, Robert; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book meets the need for a detailed resource that focuses on the unique challenges encountered in pediatric trauma and its clinical management. Short practically oriented chapters describe how to successfully treat a range of injuries across a variety of anatomical areas. Emphasis is placed on accounting for the injury mechanism providing recommendations on rapid assessment, initial stabilization and management strategies. Pediatric Trauma Care - A Practical Guide, comprehensively covers how to approach treating pediatric trauma patients suffering with a variety of injuries. Therefore, it is an ideal resource for all medical professionals who encounter these patients in their day-to-day practice.
1 Introduction - (Unique Factors to Pediatric Trauma).-2 Injury Prevention -- 3 Trauma Systems and Pedaitric Trauma Centers -- 4 Rural Pediatric Trauma Surgery -- 5 Disaster Management -- 6 Pediatric Trauma in Humanitarian and Deployed Settings -- 7 Initial Trauma Resuscitation -- 8 Airway Management -- 9 Management of Shock -- 10 Blood Tranfusions in Trauma -- 11 VTE Prophylaxis and Treatment -- 12 Surgical Nutrition -- 13 Thromboelastogram -- 14 Traumatic Brain Injury -- 15 Facial Injury -- 16 Neck Injuries -- 17 Spinal Injury -- 18 Thoracic Injury (Lung and Chest Wall) -- 19 Penetrating Abdominal Injury -- 20 Liver Injury -- 21 Pancreas, Gallbladder and Duodenum -- 22 Splenic Injury -- 23 Gastric Injury -- 24 Small Bowel/Colon Injury -- 25 Rectal Injury -- 26 Perineal (saddle) injury -- 27 Upper Tract Genitourinary Trauma -- 28 Lower Tract Genitourinary Trauma -- 29 Pelvic injury -- 30 Extremity Orthopedic Injury -- 31 Injuries to the Hand -- 32 Vascular Injuries to the Heart and Great Thoracic Vessels -- 33 Vascular injuries of the Abdominal Vessels -- 34 Vascular Injuries of the Extremity -- 35 Envenomation, bites and stings -- 36 Child Abuse -- 37 Hypothermia and Near-drowning -- 38 Burns -- 39 New Technologies in Pediatric Trauma.
Keywords: Pediatrics; Critical care medicine; Surgery; Pediatrics; Intensive Care Medicine; Surgery; Wounds and Injuries; Child; Infant; Wounds and Injuries -- therapy